Avaliação e alfabetização: um intertexto - Ruiz, Roseli da Silva Cordeiro (2009)
The purpose of the present work was to analyze a curricular practice: the evaluation in the context of alphabetization, regarding the intertext between the actions of alphabetizing and evaluating. The main goal was to identify significant interventions in the learning of reading and writing in the teachers practice in São Paulo state public schools. First, there was an explanation about the main changes in Brazilian educational scenario, concerning the cycles system, the implications related to institutional evaluations, the understanding of the concept of formative evaluation and the alphabetization teachers education facing the changes proposed by public policies. A historical approach of the main concepts about alphabetization was developed, and the ideal of evaluation of each period of time was described. Next, the data collected by semi structured interview provided the interpretation of the answers that had been given by the teachers. The essence of the content was analyzed in the light of controversy between concept and practice at the same time evaluation innovations were proposed under positivist ideal. Among the current practices, the sondage and the registration of writing ability evolution in portfolios were highlighted as evaluation tools. Finally, the work pointed some progress in alphabetization practice, but it also criticized the mechanicist and reductionist approach of sondage . It showed the possibility of an evaluation which must be formative from the moment it assumes the role of liberating learning